2019
DOI: 10.1194/jlr.m088245
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal oxidation of LDL alters lysosomal pH, induces senescence, and increases secretion of pro-inflammatory cytokines in human macrophages

Abstract: We have shown that aggregated LDL is internalized by macrophages and oxidized in lysosomes by redox-active iron. We have now investigated to determine whether the lysosomal oxidation of LDL impairs lysosomal function and whether a lysosomotropic antioxidant can prevent these alterations. LDL aggregated by SMase (SMase-LDL) caused increased lysosomal lipid peroxidation in human monocyte-derived macrophages or THP-1 macrophage-like cells, as shown by a fluorescent probe, Foam-LPO. The pH of the lysosomes was inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 78 publications
0
32
0
4
Order By: Relevance
“…Indeed, the lysosomal acidic environment increases the solubility of iron facilitating oxidation (Satchell and Leake, 2012). Furthermore, it has been demonstrated that LDL can be oxidized within the lysosomes of macrophages (Lamb and Leake, 1994;Ojo and Leake, 2018;Ahmad and Leake, 2019). In contrast, when LDL are incubated with copper at acidic pH its oxidation is delayed (Morgan and Leake, 1995), indicating that LDL oxidation by copper within lysosomes is unlikely to occur.…”
Section: Lysosomal Iron Metabolismmentioning
confidence: 99%
“…Indeed, the lysosomal acidic environment increases the solubility of iron facilitating oxidation (Satchell and Leake, 2012). Furthermore, it has been demonstrated that LDL can be oxidized within the lysosomes of macrophages (Lamb and Leake, 1994;Ojo and Leake, 2018;Ahmad and Leake, 2019). In contrast, when LDL are incubated with copper at acidic pH its oxidation is delayed (Morgan and Leake, 1995), indicating that LDL oxidation by copper within lysosomes is unlikely to occur.…”
Section: Lysosomal Iron Metabolismmentioning
confidence: 99%
“…Intrinsically related with this is the modification of the lysosomal pH that alters the activity of the majority of the lysosomal enzymes [ 162 ] and compromises the substrates of autophagic degradation as well as the endocytic cargo in senescent lysosomes [ 163 , 164 , 165 ]. Most interestingly, it has been recently shown that lysosomal oxidation of aggregated LDL alters the lysosomal pH, inducing cellular senescence and increasing secretion of pro-inflammatory cytokines in human macrophages [ 166 ]. These findings reinforce once more the active contribution of senescent lysosomes and the process of cellular senescence for atherogenesis.…”
Section: Cellular Organelles In Senescent Cellsmentioning
confidence: 99%
“…the large clinical trials of a-tocopherol were ineffective. It would be desirable to conduct clinical trials of antioxidants that accumulate in lysosomes and inhibit the oxidation of LDL at acidic pH, such as cysteamine [22][23][24][25].…”
Section: Aàtoc O þX ! Nonradical Productmentioning
confidence: 99%
“…We have shown previously that LDL can be oxidised by iron in the lysosomes of macrophages [21] and that this causes the secretion of inflammatory cytokines [22]. The antioxidant cysteamine, which accumulates in lysosomes, inhibits the lysosomal oxidation of LDL [22][23][24][25] and decreases atherosclerosis in LDL receptor-deficient mice [25].…”
Section: Introductionmentioning
confidence: 98%